Synthesis, characterization and crystal structure of platinum(II) complexes with thiourea derivative ligands - Keskin, Ebru; Solmaz, Ummuhan; Binzet, Gun; Gumus, Ilkay; Arslan, Hakan (European Journal of Chemistry, 2018)
Thiourea derivatives [N-(di-n-propylcarbamothioyl)-4-fluorobenzamide (HL1) and N-(di-n-propylcarbamothioyl)-4-bromobenzamide (HL2)] and their platinum complexes have been successfully synthesized and structurally characterized by spectroscopic 1H NMR, 13C NMR, COSY, HMQC, and FT-IR techniques. The structure of both complexes was also confirmed by single crystal X-ray diffraction studies. The study of X-ray single crystal diffraction shows that the supramolecular aggregation of the complexes is stabilized via weak interactions as well as stacking interactions such as C-H⋅⋅⋅π and π⋅⋅⋅π. The cis-[Pt(L1-S,O)2 showed C–H⋯π and π⋯π stacking interactions, whereas only C–H⋯π stacking interaction was observed in cis-[Pt(L2-S,O)2]. In addition, the strong classical and non-classical intermolecular hydrogen bonds are not found in the prepared complexes. Therefore, it can be said that the C–H⋯π and π⋯π stacking interactions play an important role in the formation of supramolecular structures of the complexes.